Intratentorial lipomas with Meckel's cave and cerebellopontine angle extension. - Ruocco, M J; Robles, H A; Rao, K C; Armonda, R A; Ondra, S L (American Journal of Neuroradiology, 1995)
An unusual case of bilateral intratentorial lipomas with extension into Meckel's caves and the cerebellopontine angle is described. Surgical and histopathologic correlation demonstrate that the lipoma encased the trigeminal nerve in Meckel's caves. The origin of the lipoma from the anteromedial margins of the tentorium is discussed and correlated with a recently proposed theory for the development of intracranial lipomas.